Penggunaan Bahasa Pada Iklan Indomie - Indah Merdekawati; Restiana Restiana (Jurnal Riset Rumpun Ilmu Bahasa, 2023)
The purpose of this article aims to fulfill our task and advertising research that uses persuasive language, this research uses the literature study method and the results of the literature study method, The language used in an indomie advertisement is persuasive language, meaning that attracts the interest of the audience. Persuasive forms can be in the form of the use of language styles that can influence the mindset of the audience so that they are interested in trying and buying the products offered, the problem is that some advertisements on television now use slang, no longer using standard language